POLYBIA RUFICEPS SCHROTTKY A NEW SOCIAL SPECIES INTRODUCED TO CHILE AND FIRST RECORD OF EPIPONINI (HYMENOPTERA: VESPIDAE: POLISTINAE) (Acta Entomológica Chilena, 2022)
Polybia ruficeps Schrottky a social species of Epiponini is for the first time reported for the Chilean fauna. Presumably the wasp spread from Argentina because the nests were found near the locality ofLos Andes (V Región), on the road to Mendoza. Besides, a key for social species introduced to Chile is provided.
Keywords: Hymenoptera, Vespidae, Polybia, Chile